The impact of increased internet availability on streaming content versus linear TV in South Africa - Sekgothe, Nkele (University of the Witwatersrand, Johannesburg, 2024)
The advent of high-speed internet has revolutionized media consumption patterns globally, and South Africa is no exception. This study investigates the impact of increased internet availability on content streaming and its subsequent effect on traditional linear television viewership in South Africa. Using a quantitative research methodology, data was run up and analyzed from a diverse sample of South African media consumers. The study reveals a significant shift in media consumption preferences, with a majority of respondents favouring Over-The-Top (OTT) streaming services over conventional linear TV. This shift is attributed to various factors including the convenience, affordability, and extensive content libraries offered by OTT platforms. The findings suggest that as internet penetration continues to rise, traditional TV broadcasters may need to create and adapt to the changing landscape to remain relevant. This paper provides valuable insights for media companies, policymakers, and researchers interested in the evolving dynamics of media consumption in the digital age
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Internet; Content; Streaming; Linear Tv; OTT; Digital; UCTD; SDG-8: Decent work and economic growth